PENGARUH PEMAHAMAN SISWA PADA MATA PELAJARAN PENDIDIKAN LINGKUNGAN HIDUP ( ENVIRONMENTAL EDUCATION) TERHADAP KARAKTER PEDULI LINGKUNGAN ( STUDI KASUS PADA SISWA KELAS VII SMP N 4 KARANGANYAR TAHUN PELAJARAN 2011/2012) - Ramadhani, Irawati (PKn Progresif, 2015)
The purpose of this study was to determine whether there is influence between the understanding of Environmental Education Towards Environmental Character in First Grade student at SMP N 4 Karanganyar Academic Year 2011/2012). The research was carried out using quantitative descriptive method. The study population is the entire all second grade students at SMP N 4 Karanganyar Academic Year 2011/2012 which amounted to 229 students. The sample used by 57 students researchers. Based on the results of the study concluded that: "There is a low significant effect and positif effect between the understanding of Environmental Education Towards Environmental CharacterIn First Grade at SMP N 4 Karanganyar Academic Year 2011/2012?. Contribution of SR in 100% and contribution of SE is 0,0029%. Effect between the student?s understanding of environmental education towards environmental character show in the equation of   Y = 45,54 + 0,0017 X